2017
DOI: 10.5606/ehc.2017.55687
|View full text |Cite
|
Sign up to set email alerts
|

Is locked compressive intramedullary nailing for adult humerus shaft fractures advantageous?

Abstract: Treatment of humerus shaft fractures with locked compressive IMN provides sufficient fixation and early movement opportunity in the shoulder and elbow joints, and gives satisfactory radiological and functional results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Seventeen studies provided data on humeral shaft fractures in their population [3,5,7,9,[11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Five studies provided information regarding findings at exploration but did not provide background epidemiological fracture data [8,10,22,[25][26].…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Seventeen studies provided data on humeral shaft fractures in their population [3,5,7,9,[11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Five studies provided information regarding findings at exploration but did not provide background epidemiological fracture data [8,10,22,[25][26].…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…It is usually diaphyseal, and surgery is only indicated in case of non-union, neurovascular injuries, pathological, or open fractures, most common being multiple injuries. [1][2][3][4] In surgical techniques, although controversies remain about the fixation with intramedullary nail (IMN) or dynamic compression plating (DCP)/locking compression plating (LCP), till now plating is found to be the better surgical modality, 5,6 with high union rates. [1][2][3] In a metaanalysis of randomized controlled trials, where plating was compared with IMN of humeral shaft fractures, it was found that the former has a low risk of complications and requires lesser clinical expertise.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Intramedullary nails (IMNs) are a good alternative to plate fixation, offering less disruption to the blood supply due to reduced periosteal dissection, smaller scars, and lower refracture rates after the removal of the implant, [12] while new generation locked IMNs exhibit high union rates. [13,14] In this study, we aimed to compare the radiological and functional results of adult patients with isolated ulnar diaphyseal fractures treated with plate and new-generation locked IMN.…”
mentioning
confidence: 99%